Implementasi Kurikulum Merdeka Belajar dalam Meningkatkan Strategi Pembelajaran dan Penguatan Pendidikan Karakter di SMA Negeri 2 Kikim Tengah - Ningsih, Deni Restu; Ahyani, Nur; Putra, Muhammad Juliansyah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research uses a descriptive qualitative approach, which is a research method used to examine natural objects. Where the researcher is the key instrument. Data collection techniques were carried out using observation, interviews and documentation. Data analysis through data reduction, data presentation, drawing conclusions or verification. The aim of this research is to find out how the independent learning curriculum is implemented at SMA Negeri 2 Kikim Tengah, as well as improving learning strategies and strengthening character education. The research results show that the independent learning curriculum at SMA Negeri 2 Kikim Tengah has been implemented at the independent learning stage. This implementation was initiated by the school principal and teachers with enthusiasm for learning and support from existing resources. Several obstacles in implementing the curriculum were found to be able to be overcome with various efforts and enthusiasm to develop the quality of education. The learning strategies at SMA Negeri 2 Kikim Tengah have improved along with the implementation of the Merdeka curriculum in learning. Teachers always try to provide a learning environment that is centered on students. Apart from that, the development of student character education in the Merdeka curriculum and the 2013 curriculum is in harmony, namely being based on the moral values ​​of Pancasila. Strengthening character education at SMA Negeri 2 Kikim Tengah is increasing along with the implementation of the independent learning curriculum which is developed through intracurricular, co-curricular and extracurricular activities.